2023
DOI: 10.3390/cells12060962
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Assessing Endothelial Dysfunction in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common degenerative disorder in the elderly in developed countries. Currently, growing evidence is pointing at endothelial dysfunction as a key player in the cognitive decline course of AD. As a main component of the blood–brain barrier (BBB), the dysfunction of endothelial cells driven by vascular risk factors associated with AD allows the passage of toxic substances to the cerebral parenchyma, producing chronic hypoperfusion that eventually causes an inflammatory and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 147 publications
0
6
0
Order By: Relevance
“…Moreover, we expect that COVID-19 infection will lead to an elevation in circulating reactive oxygen species (ROS), proinflammatory cytokines, and biomarkers of endothelial dysfunction. Elevation in these molecules have a deleterious effect on the vasculature [ 91 ] and is implicated in the development of cognitive decline and dementia [ 103 , 109 ]. Furthermore, evidence suggests that following recovery of COVID-19 infection, there is a prolonged thromboinflammatory response, in part, mediated by systemic endothelial dysfunction [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we expect that COVID-19 infection will lead to an elevation in circulating reactive oxygen species (ROS), proinflammatory cytokines, and biomarkers of endothelial dysfunction. Elevation in these molecules have a deleterious effect on the vasculature [ 91 ] and is implicated in the development of cognitive decline and dementia [ 103 , 109 ]. Furthermore, evidence suggests that following recovery of COVID-19 infection, there is a prolonged thromboinflammatory response, in part, mediated by systemic endothelial dysfunction [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence points towards endothelial impairment as a key mediator in the progression from cognitive decline to dementia. Molecules represented in the cardiovascular disease panel have been reported as biomarkers of endothelial dysfunction in vascular diseases [ 102 ] and dementia [ 103 ]. Additionally, higher levels VCAM-1 and ICAM-1 were able to differentiate AD vs MCI [ 104 ].…”
Section: Methodology and Data Analysismentioning
confidence: 99%
“…This allows nanoparticles to "leak" passively into the brain. Studies have also shown that the proinflammatory microenvironment in AD brain results in an inflamed endothelium that expresses elevated levels of cell adhesion molecules, including VCAM-1, ICAM-1, and P-selectin (Custodia et al, 2023;Grammas, 2011;Tarawneh et al, 2022;Zhang & Mao, 2020). Nanoprobes targeting overexpressed cell surface receptors can be exploited for trafficking imaging reporters into the brain.…”
Section: Nanoprobe Platforms For Molecular Imaging Of Alzheimer's Dis...mentioning
confidence: 99%
“…A postmortem study estimated that approximately 80% of people with AD have vascular pathology (55). Extensive research has shown that vascular impairment leads to reduced cerebral blood flow, endothelial damage, BBB leakage, demyelination, and cerebral atrophy, all of which can contribute to AD pathology and clinical decline (56,57).…”
Section: Vascular Dysfunctionmentioning
confidence: 99%